KARAKTERISASI KOPI BUBUK DARI BERBAGAI KATEGORI MUTU BAHAN BAKU KOPI ROBUSTA (Coffea robusta) (The Characterization of Coffee Powder from Various Quality of Robusta Coffee Bean (Coffea robusta)) - Gafar, Patoni A (Baristand Industri Banda Aceh, 2014)
The study of the characterization of robusta coffee powder (Coffea robusta)from various quality of green bean coffee had been carried out. The study aimed to getdata and information of charracteristics of robusta coffee powder from various quality ofraw material. The study applied completely randomized design with quality category ofgreen bean as treatment (T1, T2 and T3). Parameters observed were moisture, ash content,ash alkalinity and coffee extract. The result showed that the water contents were 3.4-4.3%(w/w), ash content of 2.9-7.7% (w/w), ash alkalinity of 40-64 mlNaOH/100 g and coffeeextract of 24-54% (w/w). Compare with quality requirements of SNI 01-3542-2004, thecoffee powder from green bean category of T1 and T2 fulfill the quality standard for allparameters tested. Whereas the coffee powder of T3 green bean quality category had toohigh ash content, those were 5.9-7.7% (b/b), at SNI standard requires the maximum ashcontent of 5%.